Association of maternal mental health and drinking/smoking with adolescents’ mental health based on the Korea National Health and Nutrition Examination Survey - Lee, Junghan; Song, Kyungchul; Jeon, Soyoung; Lee, Hye Sun; Lee, San; Kim, Ho-Seong; Chae, Hyun Wook (Frontiers in Psychiatry, 2023)
Introduction Depression is one of the major concerns in adolescence, with a global prevalence of approximately 5%. Diverse environmental factors can affect the development of depression depending on the individual developmental stage. Methods Using data from the Korea National Health and Nutrition Examination Survey (KNHANES), we aimed to investigate the association between socioeconomic factors and mental health in a population of non-clinically ill adolescents in Korea totaling 6,261 adolescents aged 12–18 years. Results Drinking, smoking, stress, depressed mood, suicidal ideation in adolescents, and stress, depressed mood, and suicidal ideation in mothers were identified as factors associated with adolescent depression. In addition to depressed mood and suicidal ideation, the higher perception of stress in mothers was related to higher stress perception, depressed mood, and suicidal ideation in adolescents. The association of adolescents’ mental health with fathers’ mental health was weaker than that with mothers’ mental health. Additionally, increased smoking and drinking were commonly reported in adolescents with higher stress perception, depressed mood, and suicidal ideation. Discussion We conclude that close monitoring of mental health is required for adolescents with drinking and smoking habits and mothers with mental health problems.